The utility of HepG2 cells to identify direct mitochondrial dysfunction in the absence of cell death. Issue 4 (June 2015) - Kamalian, Laleh; Chadwick, Amy E.; Bayliss, Mark; French, Neil S.; Monshouwer, Mario; Snoeys, Jan; Park, B. Kevin
Highlights Short substitution of glucose with galactose in HepG2 media reveals mito-toxicity. Parallel ATP/cytotoxicity measurement provides a mitochondrial functional endpoint. A sensitive, cost-effective and fast first tier mitochondrial screen is proposed. HepG2 cells are a better model than fresh human hepatocytes to define mito-toxicity.